2013
DOI: 10.1136/heartasia-2012-010194
|View full text |Cite
|
Sign up to set email alerts
|

Knots in the cath lab, an embarrassing complication of radial angiography

Abstract: Most case reports or series describe knots in the venous system such as knots of Swan-Ganz catheters, pacing wires or thermodilution catheters. Knots during radial angiography are relatively rare. Here we describe a simple method of unravelling a radial knot via the femoral route, together with a review of the literature on knots in the catherisation laboratory and the techniques to deal with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Catheter knotting during coronary angiography is an uncommon, but a recognised complication 1. It usually occurs through excessive manipulations of a catheter in an attempt to cannulate the right coronary artery (RCA) 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catheter knotting during coronary angiography is an uncommon, but a recognised complication 1. It usually occurs through excessive manipulations of a catheter in an attempt to cannulate the right coronary artery (RCA) 1.…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs through excessive manipulations of a catheter in an attempt to cannulate the right coronary artery (RCA) 1. Despite being an important complication, there is little reported literature regarding its best management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the Expert opinion by Gupta et al regarding the knots in the cardiac catheterisation laboratory and appreciate their efforts to overcome the complication during transradial coronary angiography 1. The authors have mentioned that patients above 70 years of age tend to have more tortuous vessels; therefore, femoral approach is preferred, but studies have shown that the rate of major complications is significantly low by transradial approach as compared with transfemoral approach in elderly patients 1–4.…”
mentioning
confidence: 99%
“…The authors have mentioned that patients above 70 years of age tend to have more tortuous vessels; therefore, femoral approach is preferred, but studies have shown that the rate of major complications is significantly low by transradial approach as compared with transfemoral approach in elderly patients 1–4. Although a higher level of expertise is required for the elderly as compared with younger patients, most of the percutaneous coronary diagnostics and interventions can be performed via the radial approach in elderly patients by selecting good equipment and continuous pressure monitoring (to diagnose kinking).…”
mentioning
confidence: 99%